2020
DOI: 10.1007/s12182-020-00435-z
|View full text |Cite
|
Sign up to set email alerts
|

Insight into selection of appropriate formulation for colloidal gas aphron (CGA)-based drilling fluids

Abstract: Application of lightweight drilling fluids is essential to develop depleted hydrocarbon reservoirs. Recently, colloidal gas aphron (CGA)-based fluids have been introduced for such applications due to their ability in controlling fluid losses. In this work, a comprehensive experimental study was performed to choose the best formulation for CGA fluids by implementing static stability tests, rheological behavior measurements, and bubble size analyses of CGAs. Xanthan gum polymer and sodium dodecyl benzene sulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Figure 7b demonstrates that the bubble size distribution shifted slightly toward the lower diameter direction as the XG polymer concentration was raised. It is also apparent that the distribution became narrower with increases in the XG polymer concentration, in agreement with literature reports [14,29,42]. This effect is attributed to increases in the viscosity of the solution along with the polymer concentration such that the migration of CO2 was inhibited and smaller bubbles were obtained.…”
Section: Effect Of Xg Polymer Concentrationsupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 7b demonstrates that the bubble size distribution shifted slightly toward the lower diameter direction as the XG polymer concentration was raised. It is also apparent that the distribution became narrower with increases in the XG polymer concentration, in agreement with literature reports [14,29,42]. This effect is attributed to increases in the viscosity of the solution along with the polymer concentration such that the migration of CO2 was inhibited and smaller bubbles were obtained.…”
Section: Effect Of Xg Polymer Concentrationsupporting
confidence: 90%
“…Longe [27] and Jauregi et al [28] evaluated the effects of the amount of surfactant on the stability of CGAs, and both concluded that increasing the surfactant concentration improved the CGA stability. Pasdar et al [29] showed that increased viscosity also enhanced the stability of CGAs. Arabloo et al [30] performed static drainage tests and observed that the amount of a xanthan gum (XG) polymer in the CGA dispersion played an essential role in conferring stability.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have found that CGA half-lives vary on the order of approximately 1.5-8 min for CGAs solely comprised of water, surfactant, and air (Molaei & Waters, 2015). Pasdar et al (2020) found that the addition of polymers could significantly increase CGA stability for use as a drilling fluid with resulting half-lives on the order of approximately 1500-2500 min. While more stable than simple gas bubbles, CGAs will eventually coalesce back into a liquid phase, resulting in a concentrated layer containing surfactant, water, and the compounds that were previously adsorbed to the CGAs.…”
Section: Introductionmentioning
confidence: 99%
“…Aphrons generated by surfactants and polymers are micro-bubbles with particle size of ~100 μm, which are composed of a gas core, two surfactant films and a viscous water film. This unique structure enables the aphrons to be stable for a long time and the compressive strength is 10 times higher than that of conventional bubbles [2,4]. The type and concentration of foaming agents have a significant impact on the aphron stability, bubbles size distribution, rheology, and filtration control ability of CGA drilling fluids, especially at high temperatures [5,6].…”
Section: Introductionmentioning
confidence: 99%